Die herlewing van sekulêre spiritualiteit in Europa en die implikasie daarvan vir die NG Kerk in Suid-Afrika - Kok, Jacobus (HTS teologiese studies, 2021)
The revival of secular spirituality in Europe and its implication for the Dutch Reformed Church in South Africa. This article critically reflected on the insights of David Tacey in which he notes that there is currently a revival in post-secular spirituality in the West, but that its deep religious roots are lacking. What would be the implication of these trends for the South African religious landscape where traditional mainstream churches such as the Dutch Reformed Church are shrinking significantly? People often say yes to God, but no to the church. Some in the church may totally renounce God. What lessons could be learned by the South African mainstream churches and theology if these trends in the West were taken into account? In this article a critical literature review (desk research) was done and the study was structured as follows: In the first place, the implication of superdiversity, supermobility and the reality of a post-COVID-19 consciousness was discussed. Next we engaged in research by scholars in which it was shown that our time, at least in the West, is characterised by existential anxiety and uncertainty. Thirdly, we engaged in the insights of David Tacey in which he also argued the fact that the uncertainty of the time in which we live, often causes people to return to spirituality. Finally, the implication of these trends for the Dutch Reformed Church in South Africa was reflected on.Contribution: This research makes a contribution to the nature and scope of the journal, in that it finds that the rise in secular spirituality, in the context of anxiety and uncertainty in a post-COVID-19 world, provides an opportunity for the Dutch Reformed Church to find meaning and significance.